Pembinaan Anak Asuh Di Asrama Bukit Pengharapan Yayasan Training Centre Kecamatan Sekayam Kabupaten Sanggau - Selena, Selena (UNIVERSITAS TANJUNGPURA, 2014)
This research aims to knowing and get information about the guidance to foster children in girl’s dormitory homestead love at sanggau district. The method used is descriptive method. research sites is girl’s dormitory homestead love at sanggau district. research subjects are 1 builder and 8 foster children. data collection techniques used are observation, interview and documentation study. Concluded of the research result is guidance to foster children in girl’s dormitory homestead love mounth hope training centre sekayam subdistrict of sanggau district has beenimplemented with good. As for the step in guidance process, education and skills development activities have also been implemented.Keywords: Guidance, Foster Children.